The impact of interval vs. continuous training on troponin and natriuretic peptide levels in post-myocardial patients: a randomised control trial. (3rd October 2022) - Novakovic, M; Bozic Mijovski, M; Trsan, J; Kosuta, D; Krevel, B; Tasic, J; Rajkovic, U; Fras, Z; Jug, B
Abstract: Introduction: High-intensity interval training (HIIT) and moderate-intensity continuous training (MICT) are two well established and used exercise modalities for cardiac rehabilitation in patients after myocardial infarction. However, data on their effects on clinically relevant biomarkers, e.g. troponin and N-terminal pro-brain natriuretic peptide (NT-proBNP) levels are scarce. The aim of the study was to assess the acute and long-term effects of HIIT vs. MICT on troponin and NT-proBNP levels in patients after myocardial infarction. Methods: Patients referred to cardiac rehabilitation after myocardial infarction were randomised to either HIIT or MICT. HIIT consisted of 7 cycles of 1.5 min of 80–90% VO2peak and 3 min of 65–70% VO2peak intensity; MICT consisted of 32 min of 75% VO2peak intensity. We have determined troponin and NT-proBNP levels before (resting), immediately after, and one hour after (a) the first and (b) the last exercise training session, in order to appraise the specific effects of HIIT vs. MICT on an acute and long-term response to training. Cardiopulmonary exercise testing was performed in all patients. Wilcoxon signed-rank test was used to compare two related samples. Results: One hundred six patients were included (55±10 years of age, 20% females), 53 in each group. There were no differences between HIIT and MICT groups in baseline characteristics. Both HIIT and MICT caused the release of NT-proBNP levels during the first exercise training session (from median 159 to 169 ng/L, p<0.001 for HIIT; from median 217 to 226 ng/L, p<0.001 for MICT), while only HIIT additionally lead to an elevation in NT-proBNP levels even 1 hour after the first session of the exercise training programme (from median 169 to 182 ng/L, p=0.002). After 36 sessions of the exercise training programme, this trend of a further increase in NT-proBNP levels was not present. Neither HIIT nor MICT raised troponin levels during both the first and the last exercise training visit. After both types of exercise (during recovery), however, a decrease in troponin level was present and was significant, but only after the first training visit (from median 10.5 to 10.0 ng/L, p=0.014 for HIIT; from 13.1 to 12.4 ng/L, p=0.035 for MICT). Interestingly, MICT, but not HIIT, caused a significant increase in troponin levels after the termination of the last exercise training visit (from median 10.5 to 10.9 ng/L, p=0.004). Conclusion: Both HIIT and MICT significantly cause an acute increase in NT-proBNP levels, while only HIIT is associated with further elevation of NT-proBNP levels after the termination of the first exercise training session in patients after myocardial infarction. On the contrary, neither exercise training modality causes a significant increase in troponin levels, suggesting that the safety pattern of both exercise training modalities may be comparable. Funding Acknowledgement: Type of funding sources: None.